Support effects of copper containing catalysts on methanol dehydrogenation - Jung, KD; Joo, OS (KOREAN CHEMICAL SOC, 2002)
CuO/ZnO, CuO/SiO2, and CuO/ZrO2 catalysts were prepared for investigating the support effects on methanol dehydrogenation. It was found that the conversion of methanol was proportional to the copper surface area on Cu/ZnO catalysts and was independent on that on Cu/ZrO2 and Cu/SiO2. The highest copper surface area was obtained with the Cu/ZrO2 (9/1). The unusual deactivation of the Cu/ZnO, which showed the highest selectivity among the catalysts tested, was observed. Pulse reaction with methanol indicated that the lattice oxygen in ZnO could be removed by forming CO2 in the catalytic reaction, supporting that the ZnO reduction was responsible for the severe deactivation of the Cu/ZnO.
Keywords: METHYL FORMATE; ION-EXCHANGE; REDUCTION; HYDROGEN; CU/ZNO; ZNO